2022
DOI: 10.1297/cpe.2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 predispose patients to type 1 diabetes mellitus?

Abstract: The incidence of COVID-19 in newly diagnosed pediatric patients with type 1 diabetes was the same as that in healthy children.• The incidence of diabetic ketoacidosis in newly diagnosed pediatric patients with type 1 diabetes was high during the pandemic period (63.2%).• We found no association between COVID-19 and new-onset pediatric type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…This consistent percentage of patients was however not significantly different respect to that found in healthy controls without diabetes collected in the same pandemic period of time (8.4%). Our data confirm the results of other studies [ 3 , 9 , 10 ], where no significantly different SARS-CoV-2 antibody frequencies were found between T1D patients and healthy controls. Salmi et al [ 10 ], with a baseline prevalence of their own region of 0.6%, did not detect SARS-CoV-2 antibodies in any of the 20 newly diagnosed T1D children recruited in the pandemic period April–October 2020.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This consistent percentage of patients was however not significantly different respect to that found in healthy controls without diabetes collected in the same pandemic period of time (8.4%). Our data confirm the results of other studies [ 3 , 9 , 10 ], where no significantly different SARS-CoV-2 antibody frequencies were found between T1D patients and healthy controls. Salmi et al [ 10 ], with a baseline prevalence of their own region of 0.6%, did not detect SARS-CoV-2 antibodies in any of the 20 newly diagnosed T1D children recruited in the pandemic period April–October 2020.…”
Section: Discussionsupporting
confidence: 92%
“…However, to date, no compelling evidence emerged to confirm a role of COVID-19 as a potential trigger of T1D, and it remains unclear whether there is a causal role of SARS-CoV-2 infection in a change of diabetes incidence. In particular, to our knowledge, no data are available on the effects of COVID-19 infection on the development of T1D autoimmunity and few, discordant information are available on SARS-CoV-2 antibody frequencies at diagnosis of T1D during pandemic, with percentages of positive patients ranging from 0 to 19% [ 3 , 8 10 ]. Based on these considerations and to gain new insights on the relationship between COVID-19 and T1D, aims of our study were:…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV2 antibody test was positive in 3 patients with T1D and 6 controls, therefore demonstrating that the positivity rate did not significantly differ between the two groups. Thus, our data did not support a clear association between previous SARS-CoV2 infection and T1D onset, similarly to previous reports ( 53 ). ( Figure 5 ) Not only infectious agents but also psychosocial stressors are known to play a fundamental role in the pathophysiology of T1D initiation, since several physical catastrophic events have been reported to be followed by an increased number of newly diagnosed cases of T1D ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 73%
“…Apart from COVID-19, the annual mortality rate for diabetic ketoacidosis is approximately 5%, which may explain why diabetic patients have higher mortality rates with COVID-19 than patients without diabetes [46]. In a study of 106 pediatric patients with a recent diagnosis of T1DM, 58.5% had diabetic ketoacidosis at baseline; when matched to control patients without T1DM, it was found that the incidence of COVID-19 infection was similar in both groups although the incidence of diabetic ketoacidosis was higher in the T1DM patients [47].…”
Section: Diabetic Ketoacidosismentioning
confidence: 99%